Integrating Emotional Intelligence and Mental Education in Sports to Improve Personal Resilience of Adolescents - Eddy Marheni; Afrizal S; Eko Purnomo; Jermaina Nina; Firunika Intan Cahyani (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Adolescents are the nation's future leaders, so their immediate environment, including their families, schools, and the government, must promote a healthy environment for them both physically and mentally. This is necessary because improving an adolescent's psychological condition is one of the most crucial investments for raising a good generation, but more and more young people are developing psychological disorders. This study employed a pseudo-experiment method of research. The findings of the study in the treatment group, as shown in the "Paired Samples Test" output table above, indicate that the t count negative value is -45,020. This difference between the average Pre-Test and the average Post-Test is what causes the t count negative value to be negative. A negative t-count may turn positive in this situation. As a result, the computed t-value is 45,020. While in the control group, it is evident from the "Paired Samples Test" output table above that the negative value t count of -7,760 t counts is due to the average Pre-Test value being lower than the average Post-Test value. A negative t-count may turn positive in this situation. Consequently, the computed t value is now -7.760. Despite the fact that both groups have an impact on pre- and post-test results, the outcomes can be seen if there is a sizable difference between the treatment and control groups. This demonstrates that the treatment group receiving mental education achieves greater results than the group not receiving such treatment. Teenagers' pre-test and post-test personal endurance results for each group show this.